Multidisciplinary approach in periodontics: Planning and treatment of complex cases - Case series - Fatemah Al-Kandari; Sami Al-Qahtani; Abdullah Al-Hawwas (Wolters Kluwer Medknow Publications, 2024)
The aim of this case series is to show the management of complex cases by combining different surgical procedures from different dental specialties. Addressing complex cases with an interdisciplinary approach provides the best treatment outcome. This approach helps in reducing the cost, time, and postoperative sequelae. The presented three clinical cases showed a combination of surgical procedures such as aesthetic crown lengthening, lateral ridge augmentation, apical surgery, and implant placement. They also showed that using bone grafting during the apical surgery improved the healing.